Effect of β-Blocker in Treatment-Naïve Patients With Advanced Lung Adenocarcinoma Receiving First-Generation EGFR-TKIs - Chang, Chia-Hao; Lee, Chih-Hsin; Ko, Jen-Chung; Chang, Lih-Yu; Lee, Ming-Chia; Zhang, Jun-Fu; Wang, Jann-Yuan; Shih, Jin-Yuan; Yu, Chong-Jen (Frontiers in Oncology, 2020)
Abstract Background: Through activation of adrenergic receptors, chronic stress can trigger the secretion of neurotransmitters and hormones that enhance tumor growth, increase angiogenesis, and promote drug resistance. This study aimed to evaluate the effect of β-blockers in patients receiving first-line epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) for lung adenocarcinoma. Methods: This retrospective cohort study enrolled patients with advanced lung adenocarcinoma under first-line EGFR-TKIs between 2011 and 2014 in the National Health Insurance Research Database of Taiwan. The effects of β-blockers use, defined as ≥60 defined daily doses within 180 days before initiation of EGFR-TKI therapy, on the 2-year time-to-discontinuation (TTD) of EGFR-TKIs and 4-year overall survival (OS) were investigated using Cox regression analyses with inverse propensity score weighting and sensitivity analysis in subgroup without hypertension and ischemic heart diseases. Results: Among 4988 enrolled patients, 552 (11.1%) were in the β-blocker group. Patients in the β-blocker group were more likely to be older than 75 and had diabetes mellitus and cardiovascular comorbidities. In Cox regression analysis, β-blocker usage was associated with a longer TTD (hazard ratio, HR: 0.91 [0.86–0.96]) and OS (HR: 0.68 [0.64–0.72]). The results also favored β-blocker group in sensitivity analysis. Conclusions: In treatment-naïve patients with advanced lung adenocarcinoma under first-line EGFR-TKIs, prior use of β-blocker was associated with a better outcome. The findings encourage further prospective clinical study to validate the possibility of β-blockers as adjuvant anticancer therapy.